Robust Biomass‐Derived Carbon Frameworks as High‐Performance Anodes in Potassium‐Ion Batteries. Issue 7 (5th December 2022) - Chen, Jintao; Chen, Guanxu; Zhao, Siyu; Feng, Junrun; Wang, Ryan; Parkin, Ivan P.; He, Guanjie
Abstract: Potassium‐ion batteries (PIBs) have become one of the promising candidates for electrochemical energy storage that can provide low‐cost and high‐performance advantages. The poor cyclability and rate capability of PIBs are due to the intensive structural change of electrode materials during battery operation. Carbon‐based materials as anodes have been successfully commercialized in lithium‐ and sodium‐ion batteries but is still struggling in potassium‐ion battery field. This work conducts structural engineering strategy to induce anionic defects within the carbon structures to boost the kinetics of PIBs anodes. The carbon framework provides a strong and stable structure to accommodate the volume variation of materials during cycling, and the further phosphorus doping modification is shown to enhance the rate capability. This is found due to the change of the pore size distribution, electronic structures, and hence charge storage mechanism. The optimized electrode in this work shows a high capacity of 175 mAh g −1 at a current density of 0.2 A g −1 and the enhancement of rate performance as the PIB anode (60% capacity retention with the current density increase of 50 times). This work, therefore provides a rational design for guiding future research on carbon‐based anodes for PIBs. Abstract : Biomass‐derived multiwalled carbon nanotubes (CNTs) hydrothermally reacts with glucose followed by P‐atom doping to produce low‐cost, sustainable materials as high‐performance anode for potassium‐ion batteries (PIBs). The increased amount of P atom doping in the glucose CNTs (GCNTs) materials can largely enhance the rate compatibility at 5 A g −1 . The phosphorus‐doped glucose carbon nanotube (PGCNT) as anode materials has great potential in high‐rate applications for energy storage.